PROSES PENGANGGARAN DI ORGANISASI PEMERINTAHAN KELURAHAN RUNGKUT MENANGGAL SURABAYA - Muhamad Risa Farhan; Narisyah Evita Zharah; Gabrena Septi Aulia; Rindu Reza Budiarti; Sheva Rajaby Eliya Trenggono; Fajar Syaiful Akbar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The budgeting process at the urban village level is critical to ensure that public services are effective and budgets are spent accountably. This study aims to analyze the budgeting process in the Village of Rungkut Menanggal, Surabaya, focusing on the stages of budget planning, implementation, and accountability. Using a descriptive qualitative method and a case study approach, data was collected through interviews, and documents. The results showed that the budgeting process in the village of Rungkut Menanggal has run in accordance with established procedures. Each stage of budgeting is well implemented, from planning to reporting, which ensures transparency and accountability of budget use. In conclusion, budget management in this village shows high effectiveness and contributes positively to public services. This research is expected to serve as a reference for other urban villages in improving their budgeting and financial management processes.